2020
DOI: 10.9734/ajaar/2020/v12i330082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strain and Skip-a-day Feed Restriction on Carcass Characteristics of Cocks at 16th Week of Age

Abstract: Feed restriction has been described as a management tool to limit birds’ access to feed in order to reduce feed cost without compromising their health and meat products. The present study was undertaken to assess the effects of strain of cocks and feed restriction at different ages on carcass characteristics. The study was conducted at Teaching and Research Farm of Ekiti State University, Ado-Ekiti, Nigeria for a period of 16 weeks. A total number of 180 day-old cockerels of two strains comprising Black and Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…The obtained result was in agreement with the previous findings [11,12,14]. It is however, contrary to the findings of Chukwuka et al, [15] who reported that there were significant differences among carcass characteristics of different strains of broilers.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The obtained result was in agreement with the previous findings [11,12,14]. It is however, contrary to the findings of Chukwuka et al, [15] who reported that there were significant differences among carcass characteristics of different strains of broilers.…”
Section: Resultssupporting
confidence: 89%
“…However, birds on the control (ad libitum) had the highest value of breast weight; while birds on 7 th week feed restriction recorded the least mean value of the trait. This contradicts the report of Azarnik et al, [10] who reported that there is an increase in breast weight after a feed restriction regime, but agree with Fasuyi et al, [11] who found that some carcass traits (such as bled weight, breast muscle and thigh weight) were affected by feed restriction. As regards back weight and thigh weight, the traits were not significantly affected by feed restriction regimes.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…Current revolutionary technology in livestock industry has received some quality improvements meat production, the study improvement initiatives broiler genetic potentials for growth, as taken lead high mortality to increased deposition of body fat and high prevalence of metabolic and skeletal instability rate (30). To minimized such negative effects, the results of quick genetic selection growing broilers consuming fodder ad libitum, it introduced the concept of feed restriction in develop the sector and to satisfy animals protein requirements (10). There are lots of feed restriction options open to farmers, those involved sporadic, skip-a-day feeding, diet dilution, time limits and limiting quantitative feed (5), So these various forms were all intended to enhance user productivity and weight gain for feed and lowered mortality rate.…”
Section: Introductionmentioning
confidence: 99%